2023
DOI: 10.1186/s12871-023-02006-2
|View full text |Cite
|
Sign up to set email alerts
|

Profile of liver cholestatic biomarkers following prolonged ketamine administration in patients with COVID-19

Abstract: Background To investigate the possible influence of prolonged ketamine (K) or esketamine (ESK) infusion on the profile of liver cholestatic biomarkers in patients with COVID-19 infection. Methods A retrospective analysis was performed on 135 patients with COVID-19 related ARDS who received prolonged K or ESK infusion. They were compared to 15 COVID-19 ICU patients who did not receive K/ESK while being mechanically ventilated and 108 COVID-19 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This modi cation in bile composition could potentially damage cholangiocytes. It is also suggested that the toxicity of ketamine may be associated with the altered bile composition [17][18][19][20][21]. An autopsy study had already suggested that norketamine tends to accumulate in the bile [22], and recent evidence has con rmed this by identifying the metabolites of ketamine in the biliary casts [22,23].…”
Section: Esposito Et Al Published a Comprehensive Publicationmentioning
confidence: 99%
“…This modi cation in bile composition could potentially damage cholangiocytes. It is also suggested that the toxicity of ketamine may be associated with the altered bile composition [17][18][19][20][21]. An autopsy study had already suggested that norketamine tends to accumulate in the bile [22], and recent evidence has con rmed this by identifying the metabolites of ketamine in the biliary casts [22,23].…”
Section: Esposito Et Al Published a Comprehensive Publicationmentioning
confidence: 99%
“…89 Recent reports have implicated the use of intravenous ketamine for sedation in the genesis of COVID-associated SCC, but cases have also been described in people who have not required ICU admission and sedation. 90 Less information is available on the development of COVID-associated SSC in patients with underlying CLD. However, in a study undertaken in patients with predominantly MASLD/MASH, 23% developed cholestatic liver injury while 15% developed SSC; 87 the majority had severe COVID-19, but the development of progressive cholestatic injury was independent of the severity of the underlying liver disease.…”
Section: No Pre-existing Liver Diseasementioning
confidence: 99%
“… 89 Recent reports have implicated the use of intravenous ketamine for sedation in the genesis of COVID-associated SCC, but cases have also been described in people who have not required ICU admission and sedation. 90 …”
Section: Longer Term Outcomesmentioning
confidence: 99%